Evaluation of the Effects of Helmet Therapy on Head Deformities: A Systematic Review of Literature - Mohammad Taghi Karimi; Mahsa Kavyani (Journal of Head & Neck Physicians and Surgeons)
Plagiocephaly is a common deformity of the skull. Various treatment approaches have been used for the subjects with head deformities, including use of helmet orthosis, repositioning, exercise, and only observation. The aim of this review was to check the efficiency of helmet therapy compared to other available approaches and also to check the effects of some parameters such as the duration of use, and age of the subjects on treatment of the subjects with this deformity. A search was done in some databases, including Google scholar, ISI Web of knowledge, PubMed, and Scopus. Some keywords such as plagiocephaly, posterior plagiocephaly, and occipital plagiocephaly were used in combination with positional modeling, helmet therapy, helmet orthosis, exercise, and observation. The quality of the studies was evaluated by use of Down and Black tool. Twenty-four studies were found on the mentioned keywords. The quality of the studies varied between 11 and 21. Although the efficiency of helmet therapy was more than other treatment approaches, the final outputs depend on optimal time and deformity criteria. This approach is effective, well tolerated with no morbidity. Moreover, it does not influence on the quality of life of the subjects. The efficiency of helmet therapy to correct head deformities is more than other available approaches. However, its effects depend on the age of the subjects at onset of treatment, duration of treatment, and severity of the deformity. Any side effects of this treatment method can be decreased by proper education of the subjects.